Exploration of Experiential Learning Research Trends in Education: A Bibliometric Analysis with The Openalex Database - Rahmat Saifuddin Anwar; Suryajaya Suryajaya; Suyidno Suyidno (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Experiential learning has been widely applied in education, yet a comprehensive bibliometric overview of its global research trends remains limited. This study analyzes the development of experiential learning research from 2013 to 2023, focusing on its application in education. Using bibliometric analysis, data were collected from OpenAlex and processed with Biblioshiny in RStudio. After filtering, 614 articles were analyzed. The results show that experiential learning remains relevant, especially in student-centered approaches like project-based learning, simulations, and laboratory activities. A significant annual growth rate of 20.8% was found in research on experiential learning, indicating its increasing relevance. These findings highlight the need for education policies that promote hands-on, inquiry-based learning, particularly in science education. Additionally, the analysis underscores the importance of teacher training programs to effectively implement experiential learning strategies. This study offers insights into the evolution of experiential learning research and its potential for educational innovation. Future studies should focus on evaluation methods and long-term impacts to optimize its application.